Torque Characteristic Analysis of Permanent Magnet Eddy-current Coupling with Slotted Conductor Disk - Wu Beidou; Bao Guangqing; Liu Xiaobao (Jixie chuandong)
Compared with the traditional permanent magnet eddy-current couplings,one with slotted conductor disk can force eddy current to flow under a designated route which can improve the transmitted torque and enhance the transmission performance of the device. But if a device with a unreasonable slot numbers or structure,the torque will decrease or the ripple will increase. So the over-all properties of the device will degradation,the regulation reliability will going harder. A comparative analysis of the number of the slot and structure is conducted. At the end,a reasonable slotted number is given and can provide an important reference for the design and application of the permanent magnet eddy-current coupling.